Scratch Assisted Educational Game Development on Data Presentation Material - Fitriyatul Qolbiyah; Depi ardian Nugraha; Depi Setialesmana (PRISMA, 2026)
This study aims to develop a Scratch-based educational game for data presentation materials and to determine its feasibility and student responses. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This study was conducted at SMAN Jatinunggal and involved two Mathematics Education lecturers from Siliwangi University as validators and 10th grade students as research subjects. Data were collected through validation sheets and student response questionnaires analyzed using a Likert scale. The results of the material expert validation showed that all aspects, including suitability, language accuracy, and presentation systematics, were in the very feasible category. Media expert validation on the interface display, navigation, supporting information, and learning design aspects also obtained a very feasible category. In the implementation phase, small group trials obtained a percentage of 90.42% and field trials increased to 93.66%, both of which were categorized as very practical. These findings indicate that the developed Scratch-based educational game is feasible and practical to be used as a mathematics learning medium for data presentation materials, and is able to increase students' interest and motivation in learning mathematics.